Malaysian Industrialised Building System (IBS): A review of studies - Mohd Nawi, Mohd Nasrun; Mydin, Md Azree Othuman; Abdul Nifa, Faizatul Akmar; Osman, Wan Nadzri; Anuar, Herman Shah (INSInet Publications, 2015)
In order to keep pace with the globalisation and modernlisation in 21st century, it is a needs for construction players to adopt relevant technology such as Industrialised Building System (IBS).Till date, the adoption of IBS has been actively promoting by Construction Industry Development Board (CIDB).Numerous of effort has been taken, for instance vast of research fund, training, establish standard and other marketing agenda. From literature and industry report, the adoption of IBS was proven beneficial to increase the project quality and productivity and automatically save cost and period of construction project.Yet, the trend of IBS usage in housing projects, especially in Malaysia’s northern region like Kedah and Perlis are still achieved the government goal. Thus, this paper highlights the factors causing low usage through a preliminary survey among the developers in that area. The survey is also aimed at identifying a few solutions to increase the application of IBS for the construction industry.Moreover, this paper also outline the characteristics of IBS.